PENGARUH ACUPRESSURE TITIK HT7 SHENMEN TERHADAP LATENSI DAN DURASI TIDUR PASIEN KANKER PASCA TERAPI - Werdani, Yesiana Dwi Wahyu (Sekolah Tinggi Ilmu Kesehatan Katolik St. Vincentius a Paulo Surabaya, 2023)
Abstract: Disruption of sleep latency and duration of cancer patients occurs due to multifactorial causes, one of which is a side effect of cancer therapy. The aim of this study was to analyze the effect of acupressure at the Shenmen HT7 point on sleep latency and duration of post-therapy cancer patients. The design uses a pre-experimental one-group pretest-posttest design approach. The population is 50 cancer patients at the Pucang Sewu Health Center and the Rangkah Health Center, Surabaya. A sample of 25 respondents was taken by purposive sampling according to the researcher's criteria. The instrument used was the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The results of the pre-test mean latency and sleep duration scores respectively were 1.96 + 0.61 and 1.08 + 0.86, while in the post-test conditions it was 1.12 + 0.72 and 0.56 + 0.71. The results of the Wilcoxon Signed Rank Test statistical test found that the p-value on the latency and sleep duration variables was 0.000 and 0.001, respectively, which means that there was a significant effect of giving the HT7 Shenmen point acupressure on the latency and sleep duration of post-therapy cancer patients. HT7 Shenmen stimulates the release of endorphins which cause relaxation, a feeling of calm, comfort, thereby helping to improve sleep latency and duration.